Differences in craniofacial growth of Class II individuals from different decades: A retrospective study. (11th June 2019) - Rongo, Roberto; Martina, Stefano; Bucci, Rosaria; Valletta, Rosa; D'Antò, Vincenzo; Martina, Roberto
Abstract: Objectives: To detect changes in mandibular growth between a historical group (HG) from the American Association of Orthodontics Foundation Craniofacial Growth Legacy Collection (AAOF Legacy) and a contemporary group (CG) of normodivergent or hypodivergent Class II untreated subjects. Setting and Sample Population: The sample included radiographs from the AAOF Legacy and from the University of Naples 'Federico II' collected during a previous RCT. Materials & Methods: The HG was composed of 26 individuals (around 1960) from the AAOF Legacy (15 from the Burlington Growth Study, nine from the Oregon Growth Study and two from the Michigan Growth Study) who were matched by sex, age and race with the 26 individuals of the CG (around 2010). Two lateral cephalograms obtained at T0 and T1 (12 months) were selected, and one examiner performed the cephalometric measurements according to Pancherz's method. The normal distribution of data was confirmed by the Shapiro‐Wilk test, MANOVA analysis and t test for paired and unpaired data were performed. The level of significance was set according to Bonferroni's correction. Results: At T0 and T1, the between‐group comparisons revealed greater linear dimensions for Maxillary base, Maxillary incisor and Mandibular incisor in the CG than in the HG ( P ≤ 0.002). No significant difference was found in the growth rate for linear skeletal measurement between the HG and the CG. Conclusions: In this study, the cephalometric analysis showed larger maxillary dimensions for the CG than the HG, while no differences were shown between the growth rate and direction of the two groups.